Przedmioty humanistyczno-społeczne na uniwersyteckiej uczelni technicznej – założenia i praktyka - Dydycz, Bożena; Zienkiewicz, Dariusz (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
In the article the authors analyze to what extend the participation of the University in the Bologna Process supports teaching humanities and social sciences and what difficulties it might cause. Furthermore, basing on long-term didactic experience at the University of Life Sciences and Technology, they made an initial diagnosis of students’ knowledge and skills gaps (in learning outcomes) which result from insufficient number of humanities and social sciences class hours. According to the authors, aforementioned situation is the result of underestimation and sometimes lack of understanding of the role of those subjects.